Optimization studies and compositional analysis of subcritical water extraction of essential oil from Citrus hystrix DC. leaves - Abdul Halim, Noor Amirah; Zainal Abidin, Zurina; Siajam, Shamsul Izhar; Chong, Gun Hean; Harun, Mohd Razif (Elsevier BV, 2021)
Subcritical water extraction (SWE) of essential oil (EO) from Citrus hystrix DC. leaves was optimized using response surface methodology (RSM), involving factors of particle size (0.5–1) mm, sample-to-solvent ratio (0.025–0.175) g/mL, extraction temperature (140− 180) ◦C, and extraction time (20− 40) minutes. Thus, an optimal EO yield of (2.14 ± 0.03) % (w/w) was obtained at 0.75 mm, 0.025 g/mL, 174 ◦C, and 29 min. SWE was found to yield significantly higher EO than the conventional hydrodistillation, within a shorter time. The regression model was established, presenting a significant quadratic correlation (R2 = 0.97) and adequate for predictions. SWE at 160 ◦C and 180 ◦C yielded 36 compounds, with isopulegol-dominant, exceeding SWE at 140 ◦C (21 compounds) and hydrodistillation (25 compounds). SWE with tunable temperatures not only improved the quantity of EO but was also capable of enhancing the quality because more EO compounds were extracted, offering diverse functionalities to nutraceutical sectors.